Analysis Of The Implication Of Stock Price And Exchange Rate And Stock Price In 5 Asia Pacific Countries, Before And After Crisis. - Intan Purbasari (Sains: Jurnal Manajemen dan Bisnis, 2017)
The relationship between stock price and exchange rate has an important implication for the a nation-economic-development. As the effect of the integration of money markets will force the interactive relation between macroeconomic factors.This thesis analyzes the relation between stock price and exchange rate before and after crisis in Singapore and Indonesia. This research analyzes two main problems which are the Granger Causality relation and long run relationship between stock price and exchange rate before and after global financial crisis. This research uses Granger Causality test, Cointegration test, Vector Error Correction Model (VECM), Impulse Response and Variance Decomposition.The results of this reasearch are showing a granger causality relation between stock price and exchange rate before and after global krisis. Our result support longrun relationship between stock price and exchange rate with different direction for each country. Singapore and Indonesia support international trading effect hypothesis.